Industrialisation and Deindustrialisation and the Real Divergence of the Polish Economy - Piotr WALĄG (Communications of International Proceedings, 2020)
Socio-economic processes initiated by industrialisation are leading to the natural effect of deindustrialisation in this age of development. This stage of shaping the structure of economies, particularly in terms of employment, has brought with it a wide range of ambiguities, including negative ones, from the displacement of the labour force from industry to growing wage and income inequalities, to losses in economic growth potential. The main aim of the study is to show the course of structural change processes in the conditions of Poland as an economy (subjected to systemic transformation processes), which, entering the phase of deindustrialisation, has not yet fully exhausted the potential offered by industrialisation, with still not saturated internal demand for industrial goods and unused opportunities to develop stronger comparative advantages than before and, most importantly, to reduce the very significant distance of divergence of the real economy. On the basis of a theoretical presentation of the problems of industrialisation and deindustrialisation of economies, an analysis of the conditions of the Polish economy was conducted. Simple measures were used, such as those from the first Kaldor law, measures of saturation of sectoral demand, GDP per hour worked, GDP per capita. The conclusions obtained during the analysis point to industrialisation as an important source of growth in labour productivity and income in Poland and justify the approach to reindustrialisation as an element of economic policy in the process of developmental catching up, through the faster pace of real convergence processes with the economies of highly developed countries, with which, as the results of research have shown, the Polish economy is more than 40 years apart. The fast pace of the convergence processes and the reduction of the divergence distance between the real Polish economy and those countries is a necessary condition for obtaining economic benefits from economic liberalisation.
Keywords: Industrialisation; Deindustrialisation; Reindustrialisation; Systemic Transformation; Real Economic Divergence; Economic Convergence Processes.